Interactive Tables Market to Grow at 7.77% CAGR Driven by Multi-Touch Technology in Education to 2020: RnRMarketResearch.com adds Global Interactive Tables Market 2016-2020 latest research report, the analysts forecast global interactive tables market to grow at a CAGR of 7.77% during the period 2016-2020 (PR Newswire, 2016)
Since the emergence of BYOD policies and the advent of touch screen devices in the education market, the practice of direct group interaction with a given subject matter at the touch of a finger is becoming more rampant.